Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd004289.pub4
|View full text |Cite
|
Sign up to set email alerts
|

HMG CoA reductase inhibitors (statins) for dialysis patients

Abstract: Statins decreased cholesterol levels in dialysis patients similar to that of the general population. With the exception of one study, studies were of short duration and therefore the efficacy of statins in decreasing the mortality rate is still unclear. Statins appear to be safe in this high-risk population. Ongoing studies should provide more insight about the efficacy of statins in reducing mortality rates in dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Although pleiotrophic effects of statins are generally considered to represent a class effect [15], most studies have shown a protective effect of statins in ischemia-reperfusion injury with simvastastin [16-18,21], whilst only one study used atorvastatin [40]. A previously published systematic review by our group of 5 randomised controlled trials found no significant effect of statin use on the risk of acute rejection in renal transplant recipients (relative risk 0.61, 95% CI 0.32-1.16) [41]. Data were not available to evaluate the effect of statins on DGF.…”
Section: Discussionmentioning
confidence: 99%
“…Although pleiotrophic effects of statins are generally considered to represent a class effect [15], most studies have shown a protective effect of statins in ischemia-reperfusion injury with simvastastin [16-18,21], whilst only one study used atorvastatin [40]. A previously published systematic review by our group of 5 randomised controlled trials found no significant effect of statin use on the risk of acute rejection in renal transplant recipients (relative risk 0.61, 95% CI 0.32-1.16) [41]. Data were not available to evaluate the effect of statins on DGF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the median value of the plasma S100A12 levels in the development population was used to dichotomize the data. Possible cutoff points for the other continuous variables for each laboratory test were determined according to their clinical importance using the results of previous studies and reference values [18-24]. The predictive value of the plasma S100A12 levels for two-year survival was estimated by the Kaplan–Meier analysis and evaluated using the log-rank test.…”
Section: Methodsmentioning
confidence: 99%
“…A Cochrane review, published in 2004, concluded that statins decreased serum cholesterol in dialysis patients as effectively as in the general population, but no conclusions were made about the effects of statins on cardiovascular mortality [57] .…”
Section: Therapeutic Measuresmentioning
confidence: 99%